PENGARUH GLOBALISASI TERHADAP MINAT BELAJAR SISWA DI SDN 030439 LAU MECIHO KECAMATAN TANAH PINEM KABUPATEN DAIRI PROVINSI SUMATERA UTARA - Monang P Anak Ampun; Dewi Kesuma Nasution (STKIP Subang, 2026)
This study aims to identify and describe in depth the impact of globalization specifically the use of technological devices and the internet on student learning interest at SDN 030439 Lau Meciho, Tanah Pinem District, Dairi Regency. This research uses a qualitative approach with a descriptive case study method. The research subjects involved 20 upper-grade students selected purposively based on indications of decreased learning concentration. Data collection was conducted from February 2 to 21, 2026, through participatory observation and semi-structured interviews. The results showed that globalization has a significant negative impact on students' learning interest. Easy access to gadgets without adequate parental supervision causes students to experience physical fatigue, loss of focus during lessons, and a decrease in academic participation. Students are more attracted to instant entertainment such as online games and social media compared to the learning process in the classroom. It is concluded that the restoration of learning interest requires a synergy of supervision between the school and parents, as well as the integration of character education based on local wisdom in learning